Arabic languaage learning problems among students at Ningxia university - Yu, Hoamiao (2019)
Arabic language has long been established in the Republic of China along with theentrance of Islam. Among the regions in which the Arabic language teaching isavailable in China is the Ningxia region. Even though the Arabic language in theNingxia region has begun for a long time, the Arabic language pass rate is stillrecording low percentage. Therefore, this study was conducted using a descriptiveanalysis pertaining to the problems of Arabic language learning among students atNingxia University. In addition, the objective of this study was to identify the factorsthat caused the Arabic language learning problems among students at NingxiaUniversity. The inductive method was used in the process of collecting informationwith regard to the Arabic language learning activities at Ningxia University. Thequantitative approach in this study used a questionnaire instrument as the maininstrument. The sample selection was carried out by means of a purposeful samplinginvolving 100 students of Ningxia University who were taking Arabic language.Besides that, the interview method was also performed to determine the level ofstudents' mastery in the Arabic language learning activities. The findings showed thatthere were several issues related to the Arabic language learning activities amongstudents at Ningxia University, which comprised the aspects of teaching staff,environment and pedagogy applied in the Arabic language learning activities. Theconclusion from this study indicated that these three aspects played an important rolein ensuring the effectiveness of the Arabic language learning activities at NingxiaUniversity. The implication of the study was to be able to identify the arisen problemsin the learning of Arabic language among students at Ningxia University andsubsequently provide recommended solutions to those problems which involved theaspects of teaching staff, learning environment and pedagogy used.